Psychology in Edgar Allan Poe - Del Guercio, Gerardo (Logos Verlag Berlin, 2019)
This collection offers six critical essays on the topic of psychology in Edgar Allan Poe. It came together as a response to a visible absence of this subject in recent scholarship. The volume presents Edgar Allan Poe as one of the pioneers in psychology, who often anticipated major theoretical trends and ideas in psychology in his incessant explorations of the relationship between behavior and the psyche. Scrutinizing serial killer narratives, obsessive narratives through Jungian unconscious, Lacanian Das Ding, doppelgängers, intersubjectivity, and the interrelationship between the material world and imaginative faculties, the essays reveal the richness and the complexity of Poe's work and its pertinence to contemporary culture.